Pengaruh Promosi Kesehatan Melalui Pendekatan Keluarga Terhadap Pengetahuan Masyarakat Berperilaku Hidup Bersih Dan Sehat - Rahmin Agusni (Indonesian Journal of Health Community, 2026)
Clean and Healthy Living Behavior is a critical public health indicator. In Tanjung Jabung Timur Regency, only 58.3% of households practiced clean and healthy living behavior, falling short of the 70% provincial target. Family-based health promotion is considered effective, yet quantitative evidence in the Indonesian local context is limited. Research to analyze the effect of family-based health promotion on community knowledge of clean and healthy living behavior in the working area of Sungai Lokan Public Health Center. A pre-experimental one-group pretest-posttest design was employed. A total of 97 respondents (household heads and neighborhood leaders) were selected by total sampling. Intervention consisted of two structured health education sessions (90 min each) using leaflets and flip charts. Data were collected via validated questionnaires and analyzed using the Wilcoxon Signed Rank Test. Prior to the intervention, 73.2% of respondents had poor knowledge. Post-intervention, 71.1% attained good knowledge. Wilcoxon test yielded Z = -8.521, p < 0.001, effect size r = 0.864 (large effect). Family-based health promotion significantly improved PHBS knowledge with a large effect size. It is recommended to integrate this approach into the Healthy Indonesia Program with a Family Approach program at health centers.